Weimar in Argentina: a Transnational Analysis of the 1949 Constitutional Reform - Leticia Vita (Rechtsgeschichte - Legal History, 2019)
In 1949, Argentina for the ﬁrst time incorporated a catalog of social rights and other provisions of social content into its constitution, breaking the liberal paradigm of the original constitutional text of 1853. Most of the studies on this subject in Argentina are characterized by »provinciality«. Both promoters and detractors of the constitutional amendment focus in their interpretations on the local context that led Argentina to adopt a new magna carta by the late 1940s. By contrast, this study oﬀers a transnational analysis of the 1949 constitutional reform. My global history perspective in this case serves to challenge the strong »methodological nationalism« that characterizes the more traditional studies of Peronism and of the 1949 constitutional reform in particular. Furthermore, while not denying that there were several other ideas and models that inﬂuenced the Argentine experience, I will in this essay concentrate on the impact of the Weimar constitutional experience. In particular, I will focus on cultural and linguistic translation, because not only geographical but also linguistic barriers are important. As we will see, the recognition of the scope of the provisions in Weimar’s constitution was strongly conditioned by the role played by the mediators and translators of that experience in Argentina.